Influência do Paleovale entre os rios Cuieiras e Tarumã-Mirim sobre as populações de Apistogramma sp. - Leitão, Carolina S S (Instituto Nacional de Pesquisas da Amazônia - INPA, 2016)
Landscape changes in the Amazon, such as drainage network reorganization, set important boundary conditions for the evolution of fish populations. As such, they establish mechanisms that regulate local biodiversity and its distribution in Amazon Rivers. This study aimed to relate the genetic differentiation of two populations of Apistogramma pertensis and A. gephyra with the stream capture of the Tarumã-Mirim River by the Cuieiras River in Central Amazonia. We developed 11 microsatellite markers and used a mitochondrial DNA (16S, COI and Cytb) to perform a population analyses, and to investigate the divergence time between them. Our data suggests that the stream capture imposed a physical barrier between these fish populations, which developed a genetic structure and resulted in a decrease of gene flow. Furthermore, the data also suggest an expansion of three, out of the four populations, excepting by the population of A. pertensis from Tarumã-Mirim River, which has a decreased size. Therefore, we suggest that the populations of A. pertensis and A. gephyra comprise four Evolutionary Significant Units (ESU) in the Rivers Cuieiras and Tarumã-Mirim.
Keywords: Genética de populações; Ciclídeos; Peixes